QUANTITATIVE LAND SUITABILITY EVALUATION FOR PLANNING VARIOUS SPICE COMMODITIES IN BAKUNG DISTRICT REGENCY BLITAR - M. Dito Alriza P W; Purnomo Eddie Sasongko; Siswanto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The development of spice plants on agricultural land in the Bakung sub-district requires appropriate information and data regarding the potential and suitability of land use based on the quality and characteristics of the land, so that the land can be sustainably productive. Therefore, land suitability evaluation research is needed as a guide in plant development. playing spices in Bakung District, Blitar Regency with the aim of examining land suitability for planning various spices commodities in Bakung District, Blitar Regency, as well as studying limiting factors that influence actual land suitability for planning various spice commodities in Bakung District, Blitar Regency. This research was carried out in Daffodils sub-district, Blitar districts in August 2023. The survey method uses a map scale of 1:80,000 and to determine the soil sampling points it will be carried out at a predetermined spl of 11 observation points including the villages of daffodil, Bululawang, Kedungbanteng, Lorejo, Ngrejo, Plandirejo, Pulerejo, Sidomulyo, Sumberdadi, Tumpak kepuh, Tumpak sloppy. Research results: The land folder units (SPL 10) of Tumpak Billowing village is very suitable for development for spices commodities. SPL 7 has the potential to be developed for spices commodities by providing management of NPK fertilizer applications, lime applications, and terracing construction. The land suitability class in Bakung sub-district which is very suitable (S1) for various commodities is at SPL 10, precisely in Sidomulyo Village. The limiting factors for the development of various spices commodities in Daffodils District are nutrients retention, available nutrients and the danger of erosion